Influence on general practitioners of teaching undergraduates: qualitative study of London general practitioner teachers. Issue 7218 (30th October 1999) - Hartley, Sarah; Macfarlane, Fraser; Gantley, Madeleine; Murray, Elizabeth
Abstract: Objective: To examine the perceived effect of teaching clinical skills and associated teacher training programmes on general practitioners' morale and clinical practice. Design: Qualitative semistructured interview study. Setting: General practices throughout north London. Subjects: 30 general practitioners who taught clinical skills were asked about the effect of teaching and teacher training on their morale, confidence in clinical and teaching skills, and clinical practice. Results: The main theme was a positive effect on morale. Within teacher training this was attributed to developing peer and professional support; improved teaching skills; and revision of clinical knowledge and skills Within teaching this was attributed to a broadening of horizons; contact with enthusiastic students; increased time with patients; improved clinical practice; improved teaching skills; and an improved image of the practice. Problems with teaching were due to external factors such as lack of time and space and anxieties about adequacy of clinical cover while teaching. Conclusions: Teaching clinical skills can have a positive effect on the morale of general practitioner teachers as a result of contact with students and peers, as long as logistic and funding issues are adequately dealt with.